ZC3H11A loss of function enhances NF-κB signaling through defective IκBα protein expression - Darweesh, Mahmoud; Younis, Shady; Hajikhezri, Zamaneh; Ali, Arwa; Jin, Chuan; Punga, Tanel; Gupta, Soham; Essand, Magnus; Andersson, Leif; Akusjärvi, Göran (Frontiers in Immunology, 2022)
ZC3H11A is a cellular protein associated with the transcription export (TREX) complex that is induced during heat-shock. Several nuclear-replicating viruses exploit the mRNA export mechanism of ZC3H11A protein for their efficient replication. Here we show that ZC3H11A protein plays a role in regulation of NF-κB signal transduction. Depletion of ZC3H11A resulted in enhanced NF-κB mediated signaling, with upregulation of numerous innate immune related mRNAs, including IL-6 and a large group of interferon-stimulated genes. IL-6 upregulation in the absence of the ZC3H11A protein correlated with an increased NF-κB transcription factor binding to the IL-6 promoter and decreased IL-6 mRNA decay. The enhanced NF-κB signaling pathway in ZC3H11A deficient cells correlated with a defect in IκBα inhibitory mRNA and protein accumulation. Upon ZC3H11A depletion The IκBα mRNA was retained in the cell nucleus resulting in failure to maintain normal levels of the cytoplasmic IκBα mRNA and protein that is essential for its inhibitory feedback loop on NF-κB activity. These findings indicate towards a previously unknown mechanism of ZC3H11A in regulating the NF-κB pathway at the level of IkBα mRNA export.